KOMPETENSI APARATUR SIPIL NEGARA PADA DINAS PENATAAN RUANG KOTA MAKASSAR - Muhammad Syihabuddin Taufiq; Achmad Fauzi Kusmin; Hendrawan (Jurnal Arajang, 2022)
This research aims to determine competency seen from the aspects of knowledge, skills, and attitudes of employees towards their work at the Makassar City Spatial Planning Office.The type of this research is descriptive qualitative. Data collection techniques were carried out through interviews, observation, and documentation. The research data were processed using qualitative analysis, which is data reduction, data presentation and drawing conclusionsThe results of this research show that the competence of employees at the Makassar City Spatial Planning Office is sufficient. This can be seen based on the results of the indicators of knowledge and skills However, based on attitude indicators, there are differences in the level of satisfaction among employees with their work. This needs to be considered so that employees can maximize their performance as a public service Key Word : Competency , Knowledge. Skill, Attitude